Efficacy of different disinfectants on removing Candida albicans, Streptococcus mutans and Enterococcus faecalis adhered to thermo cured acrylic resin - Calderón-Valencia, Mariella (2014)
The objective of this study was to evaluate the efficacy of three disinfectant solutions, on removing Candida albicans, Enterococcus faecalis and Streptococcus mutans adhered to thermo cured acrylic resin, Methodology: 51 pieces of thermo cured acrylic resin were prepared using wax patterns with the same dimensions (15mm x 15mm x 4mm) and subjected to a polishing system simulating complete dentures. The pieces were autoclaved (121 ° C x 15min), and then contaminated with strains of C. albicans ATCC ATCC S. mutans and E. faecalis ATCC. After contamination they were exposed to 0.5% NaClO, 0.12% chlorhexidine and an alkaline peroxide disinfectants for 5 min. Samples obtained from the resins were seeded in Petri plates and results were observed at 24 hours to verify the removal of the microorganisms. Results: The results were analyzed with Chi-square and Kruskal-Wallis tests. C. albicans and E. faecalis groups showed a statistically significant difference between the three disinfectants, p=0.001 and p= 0.000 respectively. Conclusions: NaOCl 0.5% and chlorhexidine 0.12% have a greater efficacy than effervescent tablets Corega Tabs® in removing C. albicans and E. faecalis adhered to thermo cured acrylic resin. The three disinfectants were effective in removing S. mutans